The Effect of Emotional Intelligence, Situational Leadership Style and Organizational Culture Through Organizational Citizenship Behavior (OCB) on Employee Performance PT. Paiton Operation & Maintenance Indonesia (POMI) in Probolinggo District - Fuad Zaen Muttaqin; Purnamie Titisari; Markus Apriono (Green Publisher Indonesia, 2022)
This study aims to examine and analyze the direct and indirect effects of emotional intelligence, situational leadership style and organizational culture through Organizational Citizhensip Behavior (OCB) on the performance of employees of PT. POMI. This research was conducted on permanent employees of PT. POMI with the number of respondents in this study as many as 210 people. The sampling technique used is proportional random sampling where the sample is taken proportionally from the entire existing population. The data analysis method used Path Analysis using SPSS 26 software. The results showed that directly emotional intelligence, situational leadership style and organizational culture had a positive and significant effect on Organizational Citizhensip Behavior (OCB). Furthermore, emotional intelligence, organizational culture and Organizational Citizhensip Behavior (OCB) has a positive and significant effect on employee performance, while situational leadership style has no significant effect on employee performance. Indirectly emotional intelligence, situational leadership style and organizational culture have a positive and significant effect on employee performance through Organizational Citizhensip Behavior (OCB).